2001
DOI: 10.1177/146642400112100409
|View full text |Cite
|
Sign up to set email alerts
|

The perceived benefits of singing

Abstract: Two exploratory studies are reported on the perceived benefits associated with active participation in choral singing. In the first study, 84 members of a university college choral society completed a brief questionnaire that asked whether they had benefited personally from their involvement in the choir and whether there were ways in which participation could benefit their health. A large majority of respondents agreed they had benefited socially (87%) and emotionally (75%), with 58% agreeing they had benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
79
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(102 citation statements)
references
References 18 publications
12
79
1
10
Order By: Relevance
“…Wise et al's (1992) retired choral singers (described in Other physical health) frequently reported that they enjoyed the "sense of community" (p. 1179) that comes with membership in a choir. Studies of existing university (Clift & Hancox, 2001) and community (Clift et al, 2007) choirs (described in Breathing and Hedonic well-being, respectively) reported interaction with others as a benefit of singing. In addition, younger members were more likely to endorse social aspects of the university choir (Clift & Hancox, 2001).…”
Section: Community Choirsmentioning
confidence: 95%
See 3 more Smart Citations
“…Wise et al's (1992) retired choral singers (described in Other physical health) frequently reported that they enjoyed the "sense of community" (p. 1179) that comes with membership in a choir. Studies of existing university (Clift & Hancox, 2001) and community (Clift et al, 2007) choirs (described in Breathing and Hedonic well-being, respectively) reported interaction with others as a benefit of singing. In addition, younger members were more likely to endorse social aspects of the university choir (Clift & Hancox, 2001).…”
Section: Community Choirsmentioning
confidence: 95%
“…However, similar to limitations noted earlier with respect to heart rate, baseline hedonic tone and energetic arousal appeared to be lower, and tense arousal, higher, in swimmers than in singers. Clift and Hancox's (2001) university choral singers (described in Breathing) reported perceived benefits of hedonic well-being, such as positive mood. Grape et al (2003) (described in Stress and immune responses) measured visual analogue scales of opposite emotions (sad/joyful, tense/ relaxed, listless/energetic) in professional and amateur singers before and after a singing lesson.…”
Section: Professional and Amateur Singers 'mentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies indicate a connection between singing as a means of self-expression, regulation of emotions, and health and well-being [5759]. Moreover, the availability of psychobiological methodology over the last decades such as the ambulatory assessment of humoral stress markers or functional imaging have confirmed that the experienced stress releasing effects of music have indeed a psychophysiological bases [60,61].…”
Section: Singing Emotion Regulation and Well-beingmentioning
confidence: 99%